Differential pulse adsorptive stripping voltammetry of osmium-modified peptides - Billová, Sabina; Kizek, René; Palecek, Emil (Bioelectrochemistry (Amsterdam, Netherlands), 2002)
Complexes of osmium tetroxide with nitrogen ligands were developed and used in our laboratory as probes of the DNA structure. Here, we show that the complex of osmium tetroxide with 2,2'-bipyridine (Os,bipy) can be used for modification and electrochemical detection of proteins at neutral pH. Salmon luteinizing hormone (SLH) containing two tryptophan (Trp) residues and human luteinizing hormone (HLH) containing one Trp were modified by Os,bipy and measured by differential pulse adsorptive stripping voltammetry (DPAdSV) at a hanging mercury drop electrode (HMDE). The intensity of the DPAdSV catalytic signals corresponded to the number of Trp residues in the peptide molecule. Decreasing pH of the background electrolyte from 6.6 to 3.8 led to the increase of DPAdSV signals, suggesting that at pH 3.8, the DPAdSV detection limit might be well below 1 ng/ml. Our results suggest that Os,bipy is potentially useful for chemical modification of proteins.
Keywords: Osmium; Adsorption; Electrochemistry; Peptides; peptidy; adsorpce; zvířata; Humans; Luteinizing Hormone; elektrochemie; luteinizační hormon; osmium; lidé; Animals